Gadolinium-enhanced nerve roots in lumbar disk herniation. - Crisi, G; Carpeggiani, P; Trevisan, C (American Journal of Neuroradiology, 1993)
PURPOSE To analyze contrast-enhanced features of intrathecal nerve roots in lumbar disk herniation in patients who have not had surgery and to evaluate the possible correlation with herniated disk, peridiscal enhancement, and symptomatology.METHODS Twenty patients with a syndrome of lumbar herniated disk without surgery were studied with pre- and postcontrast MR imaging.RESULTS In six patients (30%), ipsilateral intradural roots affected with large disk herniations showed consistent enhancement along their whole length, from the site of compression to the root-medullary junction. This enhancement persisted on delayed scanning. "Selective" enhancement differed from the minimal enhancement seen in normal intrathecal roots in 11 (55%) patients. Enhancement around herniated disks was a common finding (92% of patients) and did not correlate with selective or normal root enhancement (P > .05). No symptom differences were found among patients with and without selective enhancement.CONCLUSION Selective intrathecal root enhancement seems to be the direct visualization of the radiculopathy resulting from disk herniation. It is probably a transient event more likely to be noted in the acute phase. Although there is no evidence of immediate clinical utility of this finding, gadolinium-enhanced MR gives insights into the basic pathophysiologic alterations involved in degenerative disk disease.